The Role of the Spiritual Meaning System in Coping with Cancer - Visser, Anja (Religions, 2020)
Spirituality can support the adjustment process of people with cancer, by forming a meaning system that supports understanding of the cause and implications of the experience and that provides coping strategies. The different ways in which spiritual meaning systems might fulfill these roles were examined among 20 people who were treated for cancer with curative intent. Narrative interviews were held on average 16 months after cancer diagnosis. The interviews were analyzed in a two-stage process, based on a holistic content approach. The first stage led to the identification of various roles and outcomes of the meaning system. The second stage involved a comparison of these roles and outcomes between previously defined types of meaning systems. The roles identified were discrepancy, legitimation and continuation. Legitimation was associated with the outcome of integration, whereas continuation was associated with an outcome of a positive outlook toward the future. Several differences were found between types of meaning systems, regarding the extent to which and ways in which these roles and outcomes occurred. This study underscores recommendations that healthcare professionals should be aware of the different ways in which the patient's previous beliefs and experiences influence their current adaptation to serious life events.